SAT0089 Cost Minimization Observational Study after Dose Optimization in A Specialized Outpatient Clinic on Subcutaneous Biological Therapy. (10th June 2014) - Manrique-Arija, S.; Romero-Barco, C.M.; Ordoñez-Cañizares, M.C.; Ureña, I.; Cano, L.; Jimenez-Nuñez, F.G.; Nieves-Martin, L.; Mena-Vazquez, N.; Irigoyen, M.V.; Ponce, A.; Coret, V.; Belmonte-Lopez, M.A.; et al.
Abstract : Objectives: To estimate annual cost in the use of subcutaneous BT (scBT) in patients with rheumatic diseases when dose modifications are undertaken in daily practice in a specialized outpatient clinic of a tertiary hospital during 2013 and to compare the results with data obtained in 2012. Methods: Cost minimization, cross-sectional observational study.Patients with different rheumatic diseases who are following a tight control care in a specialized scBT outpatient clinic of a tertiary Spanish hospital who have been treated with BT under conventional and modified doses during 2013 were collected.Reductions in treatment dose were made at the discretion of their physician in patients who were in remission for at least 6 months.Main outcome:Reduction of annual average cost in euros in scBT used in clinical practice in 2013. Secondary variables:demographics, type of rheumatic disease, clinical and laboratory data. The cost reduction was calculated by comparing the real expenditure (after modifying treatment dose) with the theoretical costs if he had not made the adjustment. Statistical analysis:Descriptive analysis was performed. Reducing annual absolute costs and by treatment after the adequacy of dose in 2013 and the differences found between 2012-2013 were calculated. Results: A total of 204 patients were followed in the monographic scBT clinic in 2013, with 333 visits [1.58 visits/patient (min.1-max.5)]. Most patients had RA (n=123, 60.3%) and the rest were distributed among: spondyloarthritis (n=37, 17.6%), psoriatic arthritis (n=33; 16.2%), juvenile idiopathic arthritis (n=11; 5.4%) and one SAPHO (0.5%) treatments received in the outpatient clinic were:etanercept, adalimumab, golimumab, abatacept, certolizumab and anakinra. During 2013, the dose of the scBT of 43 (21.1%) patients (19 RA, 6 SpA, 16 PsA, 2 JIA) were modified in clinical practice because they reached clinical remission:DAS28[(mean (±SD)]=2.57 (0.85) or BASDAI [(mean (±SD)]=2.67 (1.59), without radiographic progression. No patients treated with golimumab, abatacept, certolizumab or anakinra was modified treatment doses. Among the 43 patients, 28 patients were treated with Etanercept and 15 with Adalimumab. The BT dose reduction in clinical practice during 2013 represented a saving of €205, 947.68 and a greater efficiency of treatments while in 2012, only 28 patients (18 etanercept and 10 adalimumab) had a modified dose of scBT in clinical practice assuming a saving of €124, 120.79. Conclusions: In rheumatic diseases we may adjust the dose of treatment in patients who go into remission reducing the associated costs of scBT and being more efficient with the treatments. A largest number of patients in dose reduction, during 2013, could be attributed to a tight-control management carried out since the creation of a specialized BT outpatient clinic. We believe it is important to create outpatient clinics specialized in BT where periodic assessments with close monitoring of these patients and an individualized treatment are carried out. Disclosure of Interest: S. Manrique-Arija Grant/research support: Pfizer, C. Romero-Barco: None declared, M. Ordoñez-Cañizares: None declared, I. Ureña: None declared, L. Cano: None declared, F. Jimenez-Nuñez: None declared, L. Nieves-Martin: None declared, N. Mena-Vazquez: None declared, M. Irigoyen: None declared, A. Ponce: None declared, V. Coret: None declared, M. Belmonte-Lopez: None declared, M. Rodriguez: None declared, A. Fernandez-Nebro Grant/research support: Pfizer, Roche, Speakers bureau: Pfizer, Roche, Abbvie, MSD, BMS DOI: 10.1136/annrheumdis-2014-eular.4525